Caracterização morfofenológica e divergência genética de frutos de cerejeira-do-rio-grande (Eugenia involucrata DC.) - Mayer, Leonardo (2021)
Brazil has one of the greatest diversities in native fruit trees, but many species, despite the great environmental and economic potential for small farms, are little studied, such as the cherry-ofthe-rio-grande (Eugenia involucrata DC.). The research hypothesis was that genetic diversity exists, since the seedling production method used by the populations is the seminal one, occurring genotypes with flowering and staggered production, with differentiated leaf and fruit characteristics. So, this study aimed to characterize leaves and, for two consecutive harvests, also the reproductive phenology and physicochemical parameters of fruits, assessing genetic divergence. Were evaluated 50 genotypes of different ages found in rural and urban areas of the municipality of Serafina Corrêa, Rio Grande do Sul. Data were submitted to determine the mean and standard deviation. To assess genetic diversity, the relative contribution of characters was determined by the Singh method; the average Euclidean distance standardized matrix (UPGMA) and dendrograms were generated, and Tocher's optimization method was applied. The results revealed that the periods of occurrence and duration of flowering, harvest, and the period between the end of flowering and beginning of harvest varied between the genotypes, within each crop, and between crops, influenced by biotic and abiotic factors. The genotypes presented differences in leaf size and a, b, and total chlorophyll contents. Some genotypes showed an alternation of production, even with flowering, possibly due to the effect of water stress combined with the genetic profile. Fruit characteristics varied from one year to another, resulting in changes from one crop to another in the most contributing characters to divergence and formation of the similar genotypes groups. The UPGMA and Tocher clustering methods are more efficient in representing the diversity between genotypes. The content of total soluble solids (TSS) in the first crop and fruit mass in the second one were the characters that most contributed to genetic divergence. It is concluded that, based on the phenological and leaf differences, but mainly on the physicochemical characters of the fruits used in the multivariate analysis, that there is genetic divergence among genotypes of cherry-of-the-rio-grande, allowing the selection of agronomically superior plants.